Assessment and Improvement of TELEMAC-2D Routines for Urban Flood Simulation - Chen, Ruijie (Université d'Ottawa / University of Ottawa, 2022)
Pluvial flood is a natural hazard that severely threatens people’s property and safety. With the development of algorithms and computer technologies, numerical modeling has emerged as an effective tool for predicting the impacts of floods. Despite being one of the most costly types of floods in West Africa, pluvial flooding has not been studied as extensively as riverine flooding, probably because modeling runoff across urban areas remains a challenge. Recently, a module based on the SCS Curve Number Method is incorporated in the open-source software TELEAMC-2D, which provides a possibility to model the infiltration process dynamically. TELEMAC-2D is one of the first hydraulic models to consider hydrologic parameters. Although the update is expected to increase the suitability of TELAMC-2D in pluvial flood modeling, the infiltration routine has not yet been tested in a real situation in a semi-arid area. This study aims to investigate the capability of TELEMAC-2D in simulating the rainfall-runoff process during a pluvial flood event in a semi-arid urban area, Niamey city in west Africa. Due to the lack of calibration data, a hydrological model SWAT is used to evaluate the performance of TELEMAC-2D. Through the comparison between the runoffs generated by the two models, it is found that TELEMAC-2D has a similar trend with SWAT in runoff simulation. However, TELEMAC-2D significantly overestimates the runoff magnitude despite having the same SCS values as SWAT. The reason for the overestimation is TELEMAC-2D that does not properly consider evaporation. Two suggestions are made to improve pluvial floods simulations using TELEMAC-2D in semi-arid areas: 1) couple TELEMAC-2D with a hydrologic model, and use net rainfall generated by the hydrologic model as precipitation input; 2) provide functions in infiltration subroutine that calculate rainfall abstractions by other hydrologic phenomena in addition to the infiltration process.
Keywords: Pluvial Flood; TELEMAC-2D; SCS Curve Number Method; SWAT